Associations of ambivalent leadership with distress and cortisol secretion - Herr, Raphael; Fischer, Joachim E.; Bosch, Jos A. (Journal of behavioral medicine, 2019)
Ambivalent social ties, i.e., whereby a relationship is evaluated simultaneously in positive and negative terms, are a potential source of distress and can perturb health-relevant biological functions. Social interactions at the workplace, in particular with supervisors, are often described in ambivalent terms, but the psychological and psychobiological impact of such interactions has received little scientific attention. The current study examined associations between ambivalent attitudes towards one's supervisor, perceived distress (general and work-related), and diurnal dynamics of the stress hormone cortisol. 613 employees evaluated their supervisor in terms of positive and negative behaviors, which was combined into an ambivalent index. Higher ambivalence was associated with higher perceived distress and work-related stress (p < .001), and with a larger cortisol awakening response and higher day-time secretion post-awakening (p < .01). The present study is the first to identify ambivalence towards supervisors as a predictor of employee distress and stress-related endocrine dysregulation. In consequence, focusing solely on positive or negative leader behavior may insufficiently capture the true complexity of workplace interactions and attempts to compensate negative behaviors with positive are unlikely to reduce distress-but quite the opposite-by increasing ambivalence.
First Online: 26 October 2018
Gesehen am 12.06.2019